First evaluation of the safety, pharmacokinetics, and pharmacodynamics of BAY 2433334, a small molecule targeting coagulation factor XIa. (19th July 2021) - Thomas, Dirk; Kanefendt, Friederike; Schwers, Stephan; Unger, Sigrun; Yassen, Ashraf; Boxnick, Stefanie
Abstract: Background: Coagulation factor XI (FXI) contributes to the development of thrombosis but appears to play a minor role in hemostasis and is, therefore, an attractive anticoagulant drug target. Objectives: To evaluate the safety, pharmacokinetic, and pharmacodynamic properties of BAY 2433334, an orally administered small molecule targeting activated FXI (FXIa), in healthy men. Patients/Methods: This phase 1 study was conducted in two parts. In part 1, 70 volunteers were randomized 4:1 to receive a single oral dose of BAY 2433334 (5–150 mg as oral solution or immediate‐release tablets) or placebo. In part 2, 16 volunteers received a single oral dose of five BAY 2433334 5‐mg tablets with or without a high‐calorie breakfast in a randomized crossover study design. Adverse events, pharmacokinetic parameters, and pharmacodynamic parameters were assessed up to 72 h after drug administration. Volunteers were followed up after 7 to 14 days. Results: BAY 2433334 demonstrated favorable safety and tolerability with a dose‐dependent increase in exposure and a terminal half‐life of 14.2 to 17.4 h. A high‐calorie breakfast reduced mean maximum plasma concentration and exposure by 31% and 12.4%, respectively. AY 2433334 was associated with a dose‐dependent inhibition of FXIa activity and an increase in activated partial thromboplastin time. Bleeding times in volunteers who had received BAY 2433334 were similar to those in volunteers who had received placebo. Conclusions: These data indicate that BAY 2433334 is a promising development candidate for once‐daily oral anticoagulation; it is being evaluated in phase 2 dose‐finding studies in patients at risk of thrombosis.